Lucrècia Borja en la premsa espanyola de 1835 a 1875. - GOMAR, MARC (Scripta, 2017)
In the period of time between 1835 and 1875, the opera (or play) Lucrezia Borgia was always running somewhere in Spain. In this research it has been considered the period of time between its first release in the Iberian Peninsula and the publication of «Lucrecia Borgia, rehabilitada». This text is a very long essay about Lucrecia's biography, written by Gregorovius, which was published in the first issue of Revista contemporánea. It needs to be considered that it was usual for journalists in that period of time to reduce, copy and paste texts, which has a multiplier effect. Lucrezia Borgia play reached an extraordinary popularity, and so it began to appear in affairs and politics columns, as well as in theatre and musical reviews columns. The same happened in the nineteenth century to other fictional characters of powerful women.